Promoting Sustainability in the Automotive Industry: Economic Comparison of Dealer Sales Model and Agency Sales Model of Electric Vehicles in Slovakia - Kovalova, Erika; Vartiak, Lukas (European Journal of Sustainable Development, 2024)
Electrification is becoming an increasingly important part of many industries. Electrification is a crucial area of interest in developing electric vehicles and charging infrastructure in the automotive industry. Research and innovation in the field of electric vehicles indicate positive trends. The rise in sales of electric vehicles represents a significant shift away from traditional fossil fuel-powered technologies to more sustainable and efficient alternatives. Electrification also brings with it new trends in sales models. The paper aims to identify recommendations for the practical adaptation of the importer of electric vehicles in the Slovak market based on the analysis of the financial and economic impacts of the sale of electric vehicles. This paper approaches two essential research topics. The first research topic focuses on the analysis of vehicle sales, specifically electric vehicles, and based on the analysis of existing sales, the paper will also outline the sales plan of the selected brand in the period 2023